SSR marker-based genetic diversity and marker-trait association analysis in aromatic rice (Oryza sativa) landraces - BURMAN, MAUMITA; NAIR, SUNIL KUMAR; SAO, ABHINAV; GAURAHA, DEEPAK; SHARMA, DEEPAK (The Indian Journal of Agricultural Sciences, 2023)
The present study on SSR marker-based genetic diversity and marker-trait association analysis in aromatic rice (Oryza sativa L.) landraces was carried out at R. H. Richharia Research Laboratory, Indira Gandhi Krishi Vishwavidyalaya, Raipur, Chhattisgarh during 2020. A total of 25 PCR-based simple sequence repeats (SSR) markers were evaluated in a set of 90 aromatic rice landraces along with 6 checks which includes 1 non-aromatic and 5 aromatic check varieties. Phenotypic data for marker-trait association analysis were taken for 24 yield attributing traits. Polymorphic Information Content (PIC) value ranged from 0.52 (RM316) to 0.79 (RM553) with a mean of 0.69 which reveals that all the markers used in this study were highly informative and useful for diversity analysis of a wide range of genotypes. Unweighted Pair Group Method with Arithmetic Mean (UPGMA) and Rho’s similarity based cluster analysis revealed that all 5 aromatic check varieties falls in one cluster while the 1 non-aromatic check variety (Mahamaya) forms a separate cluster. Mixed linear model (MLM) was applied to perform genome-wide association mapping where 41 significant marker-trait associations were observed for 24 yield attributing traits. The potential markers identified in the study may provide new opportunities for rice breeder to improve yield and its attributing traits through marker assisted selection approach.